Comparative analysis of myometrial and vascular smooth muscle cells to determine optimal cells for use in drug discovery. (August 2019) - Siricilla, Shajila; Knapp, Kelsi M.; Rogers, Jackson H.; Berger, Courtney; Shelton, Elaine L.; Mi, Dehui; Vinson, Paige; Condon, Jennifer; Paria, Bibhash C.; Reese, Jeff; Sheng, Quanhu; Herington, Jennifer L.
Graphical abstract: Abstract: Novel therapeutic regulators of uterine contractility are needed to manage preterm labor, induce labor and control postpartum hemorrhage. Therefore, we previously developed a high-throughput assay for large-scale screening of small molecular compounds to regulate calcium-mobilization in primary mouse uterine myometrial cells. The goal of this study was to select the optimal myometrial cells for our high-throughput drug discovery assay, as well as determine the similarity or differences of myometrial cells to vascular smooth muscle cells (VSMCs)-the most common off-target of current myometrial therapeutics. Molecular and pharmacological assays were used to compare myometrial cells from four sources: primary cells isolated from term pregnant human and murine myometrium, immortalized pregnant human myometrial (PHM-1) cells and immortalized non-pregnant human myometrial (hTERT-HM) cells. In addition, myometrial cells were compared to vascular SMCs. We found that the transcriptome profiles of hTERT-HM and PHM1 cells were most similar (r = 0.93 and 0.90, respectively) to human primary myometrial cells. Comparative transcriptome profiling of primary human myometrial transcriptome and VSMCs revealed 498 upregulated (p ≤ 0.01, log2FC≥1) genes, of which 142 can serve as uterine-selective druggable targets. In the high-throughput Ca 2+ -assay, PHM1 cells had the most similar response to primary human myometrial cells in OT-induced Ca 2+ -release (Emax  = 195% and 143%, EC50  = 30 nM and 120 nM, respectively), while all sources of myometrial cells showed excellent and similar robustness and reproducibility (Z' = 0.52 to 0.77). After testing a panel of 61 compounds, we found that the stimulatory and inhibitory responses of hTERT-HM cells were highly-correlated (r = 0.94 and 0.95, respectively) to human primary cells. Moreover, ten compounds were identified that displayed uterine-selectivity (≥5-fold Emax or EC50 compared to VSMCs). Collectively, this study found that hTERT-HM cells exhibited the most similarity to primary human myometrial cells and, therefore, is an optimal substitute for large-scale screening to identify novel therapeutic regulators of myometrial contractility. Moreover, VSMCs can serve as an important counter-screening tool to assess uterine-selectivity of targets and drugs given the similarity observed in the transcriptome and response to compounds.